FRANÇOIS MITTERRAND AND THE GRAY ZONE OF VICHY. Issue 2 (1st July 2019) - McDonnell, Hugh
Abstract : This article examines the 1994–1995 controversy surrounding President François Mitterrand's past involvement with Vichy France through the concept of "the gray zone." Differing from Primo Levi's gray zone, it refers here to the language that emerged in France to account for the previously neglected complicity of bystanders and beneficiaries and the indirect facilitation of the injustices of the Vichy regime. The affair serves as a site for exploring the nuances and inflections of this concept of the gray zone—both in the way it was used to indict those accused of complicity with Vichy, and as a means for those, like Mitterrand, who defended themselves by using the language of grayness. Paying attention to these invocations of the gray zone at this historical conjuncture allows us to understand the logic and stakes of both the criticisms of Mitterrand and his responses to them, particularly in terms of contemporaneous understandings of republicanism and human rights.